2014
DOI: 10.1136/bcr-2013-202572
|View full text |Cite
|
Sign up to set email alerts
|

Transient ischaemic attack secondary to paraneoplastic erythrocytosis

Abstract: A 67-year-old woman with a history of hypertension and type 2 diabetes mellitus was admitted to the hospital due to aphasia and left-sided hemiparesis during the past 5 h with resolution of symptoms within 24 h. On admission laboratory analysis showed haemoglobin 19.2 g/dL and haematocrit 55.1%. Cerebral CT scan was also performed on admission revealing periventricular leucoaraiosis. Studies to investigate the cause of erythrocytosis were started and elevated erythropoietin levels were found. In order to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…There have been few reports of vascular thrombosis, including cerebral infarction and TIAs precipitated by secondary erythrocytosis of other aetiologies 8–12…”
Section: Discussionmentioning
confidence: 99%
“…There have been few reports of vascular thrombosis, including cerebral infarction and TIAs precipitated by secondary erythrocytosis of other aetiologies 8–12…”
Section: Discussionmentioning
confidence: 99%
“…While polycythemia vera is known to be the cause of serious thrombosis, it is uncertain whether secondary polycythemia might increase the risk of thrombosis. However, as is it has been reported that secondary polycythemia might cause critical infarction or thrombosis [68], it is important to pay attention to e-cigarette smokers' polycythemia.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well-established that cancer can contribute to hypercoagulable states, acute events are not often directly correlated with elevated Epo [ 7 ]. There have been reports on transient ischemic attacks due to paraneoplastic erythrocytosis, and ischemic stroke due to secondary polycythemia of other etiologies [ 2 , 8 10 ]. Polycythemia vera, a myeloproliferative disease resulting in an elevated absolute red blood cell mass in the absence of elevated Epo, has been shown to present with acute embolic cerebral ischemia [ 11 ].…”
Section: Discussionmentioning
confidence: 99%